Links between an Owner’s Adult Attachment Style and the Support-Seeking Behavior of Their Dog - Rehn, Therese; Beetz, Andrea; Keeling, Linda J. (Frontiers in Psychology, 2017)
The aim of this study was to investigate if an owner’s adult attachment style (AAS) influences how their dog interacts and obtains support from them during challenging events. A person’s AAS describes how they perceive their relationship to other people, but it may also reflect their caregiving behavior, and so their behavior towards the dog. We measured the AAS of 51 female Golden retriever owners, using the Adult Attachment Style Questionnaire (ASQ), and observed the reactions of the dog-owner dyads in response to different challenging situations (visual surprise (VIS), auditory stressor (AUD) and social stressors like a person approaching dressed as ghost (G) or in coat, hat and sunglasses (AP)). In addition, the dog was left alone in a novel environment for three minutes. Interactions between the dog and owner were observed both before and after separation. Spearman rank correlation tests were made (between owner AAS and dog behavior) and where correlations were found, Mann-Whitney U-tests were made on the dogs’ behavioral response between high and low scoring groups of owners of the different subscales of the ASQ. The more secure the owner (ASQ subscale ‘Confidence’), the longer the dog was oriented to the two sudden stressors. The more anxious the owner (ASQ subscale ‘Attachment anxiety’), the longer the dog oriented towards the owner during the approach of the strange-looking person and the dog showed less lip licking during separation from the owner. The more avoidant the owner (ASQ subscale ‘Avoidant attachment’), the longer the dog oriented towards the owner during the visual stressor, the less it was located behind the owner during the auditory stressor and the less it was oriented towards the auditory stressor. These links between owner attachment style and dog behavior imply that dogs may develop different strategies to handle challenging situations, based on the type of support they get from their owner.